The influence of maturity status on movement quality among English Premier League academy soccer players - Ryan, D.; McCall, A.; Fitzpatrick, G.; Hennessy, L.; Meyer, T.; McCunn, R. (Sport Performance & Science Reports, 2018)
The precise timing and tempo of maturation varies between individuals, hence, it is important to consider chronological age and maturity status separately.(6) Failure to do so exposes applied practitioners and coaches to the risk of unfairly judging young players' abilities. Since assessments of movement quality are widely used within professional soccer, a greater understanding of the in uence physical maturity has on this attribute may help applied practitioners better interpret the results.(14) Aim. The aim of the present study was to determine the influence of physical maturity status on Functional Movement Screen (FMS.) score, countermovement jump (CMJ) height and 0-10m-sprint time. Additionally, the relationships between these physical tests were investigated.